Drawing a Close to the Use of Human Figure Drawings as a Projective Measure of Intelligence - Imuta, Kana (Public Library of Science, 2013)
The practice of using children's human figure drawings (HFDs) to assess their intellectual ability is pervasive among psychologists and therapists in many countries. Since the first systematic scoring system for HFDs was published in 1926, their continued popularity has led to the development of several revised versions of the test. Most recently, the Draw-A-Person Intellectual Ability Test for children, adolescents, and adults (DAP:IQ) was published. It is the most up-to-date form of HFD test designed to assess intellectual functioning across a wide age range. In the present study, we assessed the validity of the DAP:IQ as a screening measure of intelligence in both children and adults. In Experiment 1, 100 4- to 5-year-old children completed the DAP:IQ and the Wechsler Preschool and Primary Scale of Intelligence-Third Edition. In Experiment 2, 100 adults completed the DAP:IQ and the Wechsler Abbreviated Scale of Intelligence. In both experiments, we found only weak to modest correlations between scores on the DAP:IQ and the Wechsler tests. Furthermore, when we compared individual's scores on the two tests, the DAP:IQ yielded high false positive and false negative rates when screening for borderline and superior intellectual functioning. Based on these findings, and based on the lack of validity of previous HFD tests, we conclude that practitioners should not rely on HFD tests as a projective measure of intelligence.